1991
DOI: 10.1113/jphysiol.1991.sp018405
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐bridge kinetics in the presence of MgADP investigated by photolysis of caged ATP in rabbit psoas muscle fibres.

Abstract: SUMMARY1. The interaction between MgADP and rigor cross-bridges in glycerol-extracted single fibres from rabbit psoas muscle has been investigated using laser pulse photolysis of caged ATP (P3-1(2-nitrophenyl)ethyladenosine 5'-triphosphate) in the presence of MgADP and following small length changes applied to the rigor fibre.2. Addition of 465 gM-MgADP to a rigor fibre caused rigor tension to decrease by 15-3 + 0 7 % (s.E.M., n = 24 trials in thirteen fibres). The half-saturation value for this tension reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
126
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(152 citation statements)
references
References 49 publications
23
126
3
Order By: Relevance
“…At saturating ADP the reaction observed is A* ϩ M.ADP 3 AM.ADP: we still observe no working stroke and as M.ADP has been assigned to being in a rigor conformation, so must AM.ADP. This observation is in agreement with structural studies for myosin II (19), although it must be acknowledged that fiber studies have suggested that a small lever movement could still control the rate of ADP release (20). Actin binds to M.ADP and forms a weakly bound complex that Geeves (21) labeled A-MD (an A state).…”
Section: Discussionsupporting
confidence: 84%
“…At saturating ADP the reaction observed is A* ϩ M.ADP 3 AM.ADP: we still observe no working stroke and as M.ADP has been assigned to being in a rigor conformation, so must AM.ADP. This observation is in agreement with structural studies for myosin II (19), although it must be acknowledged that fiber studies have suggested that a small lever movement could still control the rate of ADP release (20). Actin binds to M.ADP and forms a weakly bound complex that Geeves (21) labeled A-MD (an A state).…”
Section: Discussionsupporting
confidence: 84%
“…5A), although the tension rise in the presence of ADP was indeed earlier and slower than control. Also, Dantzig et al (1991), who were the first to point out the ADP-related early tension rise in psoas fibres at room temperature, did not notice the biphasic nature of the contraction. However, if the experimental temperature is lowered to 8°C, even the psoas fibres exhibit clear biphasic contractions in the presence of ADP (Horiuti et al 1994b).…”
Section: Binding Of Little Adp To the Cycling Cross-bridgementioning
confidence: 97%
“…The affinity of ADP for the rigor cross-bridge was directly examined (without using caged ATP) by studying the relaxing effect of ADP on the rigor fibre (Dantzig, Hibberd, Trentham & Goldman, 1991). Figure 9A shows a typical chart record from the ADP titration experiments.…”
Section: Km For Adp Of the Rigor Cross-bridgementioning
confidence: 99%
See 1 more Smart Citation
“…Direct evidence for strain-limited ADP-release (or ATP binding) has been hard to come by for fast muscle myosins (but see Dantzig et al 1991). However, it is clear that ADP release can be important in timing cross-bridge detachment.…”
Section: Introductionmentioning
confidence: 99%